Bargaining with two-person-groups: On the Insignificance of the patient partner - Oliver Kirchkamp; Ulrike Vollstädt (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
Although many real bargaining situations involve more than two people, much of the theoretical and experimental research concentrates on the two player situation. We study the simplest possible extension: four people (two two-person groups) of different patience bargain with each other. Theoretically, only the more patient member of each group should be relevant for the outcome. The less patient members would agree to any outcome and are, hence, irrelevant. We find, however, that the impact of the patient member can be quite small.
Keywords: C78; D74; 330; bargaining experiment; heterogeneous group members; Verhandlungstheorie; Gruppenentscheidung; Test